The Impact of Personality Traits on the Outcome of Total Knee Arthroplasty. (18th February 2016) - Giurea, A.; Fraberger, G.; Kolbitsch, P.; Lass, R.; Schneider, E.; Kubista, B.; Windhager, R.
Abstract : Ten to twenty percent of patients with total knee arthroplasty (TKA) are dissatisfied with their clinical outcome. Aim of this study was to investigate the impact of personality traits on the subjective outcome of TKA. We investigated 80 patients with 86 computer navigated TKAs. We asked for patients satisfaction and divided patients into two groups (satisfied or dissatisfied). 12 personality traits were tested by the Freiburg Personality Inventory (FPI-R). Postoperative examination included Knee Society Score (KSS), Western Ontario and McMaster University Osteoarthritis Index (WOMAC), and the Visual Analogue Scale (VAS). Radiologic investigation was done in all patients. 84% of our patients were satisfied, while 16% were not satisfied. The FPI-R showed statistical significant influence of four personality traits on patient satisfaction: life satisfaction (p = 0.006 ), performance orientation (p = 0.015 ), somatic distress (p = 0.001 ), and emotional stability (p = 0.002 ). All clinical scores (VAS, WOMAC, and KSS) showed significantly better results in the satisfied patient. Radiological examination showed optimal alignment of all TKAs. There were no complications requiring revision surgery. The results of our study show that personality traits may influence patients satisfaction and clinical outcome after TKA. Therefore patients personality traits may be a useful predictive factor for postoperative satisfaction after TKA.